LEXICOGRAPHIC REPRESENTATION OF ENGLISH PAREMIOLOGICAL DICTIONARIES - Mambetalieva Ayzada Bakhitbaevna (Modern American Journals, 2025)
This study examines the principles of lexicographic representation in English paremiological dictionaries from a linguocultural perspective. The research focuses on the semantic, pragmatic, and cultural dimensions of proverb description, emphasizing the role of paremiological units as culturally marked and evaluative language elements. Drawing on the theoretical frameworks of A. Taylor, W. Mieder, A. Dundes, S. L. Arora, R. Moon, and J. Speake, the paper analyzes macrostructural and microstructural strategies used in English proverb dictionaries, including thematic organization, variant fixation, usage labeling, and cultural commentary. Special attention is given to corpus-based approaches in modern paremiological lexicography and their role in reflecting contemporary usage. Through illustrative examples from English and Karakalpak paremiological material, the study demonstrates that proverb dictionaries function not only as linguistic reference tools but also as repositories of cultural codes and national worldviews. The findings confirm that integrative lexicographic representation is essential for comparative linguocultural research.
Keywords: Paremiology; paremiological dictionary; lexicographic representation; proverb semantics; cultural interpretation; pragmatics; linguistic worldview; English proverbs; Karakalpak proverbs; comparative linguocultural analysis